Jacqueline in Paris : a novel - Mah, Ann (Mariner Books, 2022)
"From the bestselling author of The Lost Vintage, a rare and dazzling portrait of Jacqueline Bouvier's college year abroad in postwar Paris, an intimate and electrifying story of love and betrayal, and the coming-of-age of an American icon - before the world knew her as Jackie"--